ESTRATEGIA TURÍSTICA PARA LOS VISITANTES EN LA RUTA DE RÍO, CANTÓN QUEVEDO AÑO 2022. - Feran Ordoñez, Nicole Paulette (2022)
At present, Quevedo is constituted as a prosperous canton of the Province of Los Ríos, its natural environment, cultural diversity and its industrious people have established it to position itself as one of the cantons that presents one of the highest indices in terms of development. which is an attraction that influences investors to decide to invest in new projects of different kinds. The objective of this research is to analyze through which tourism strategy can be motivated so that visitors frequent the river route, Quevedo canton, tourism development has become an important growth factor, on which many Quevedo families depend, the proposal is that use traditional and alternative media to develop an advertising campaign regarding products, services and activities, for its effect and study, the investigative techniques and methods were applied through which information was obtained, concluding that it should be analyzed and corrected the type of strategies that are currently being projected on the river route, implemented, the necessary mechanisms in terms of attention to service, training, prices, promotions, gastronomic tourism, recreational activities to consumer tastes.